1975
DOI: 10.2135/cropsci1975.0011183x001500050032x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Alfalfa Which Regenerates from Callus Tissue in Culture1

Abstract: Tetraplold alfalfa (Medicago sativa L.) germplasm, in which two‐thirds of the plants are capable of regeneration from callus tissue in culture, has been developed by recurrent selection. It descends from one ‘DuPuits’ and four ‘Saranac’ clones which regenerated in the cycle 0 population. Frequency of regeneration was 12% in cycle 0, about 50% in cycle 1, and 67% in cycle 2. Seed produced by hand‐intercrossing 75 plants regenerated from cycle 2 has been termed ‘Regen‐S’ (Regen for regeneration; S for Saranac). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
3

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(73 citation statements)
references
References 0 publications
5
65
0
3
Order By: Relevance
“…Regeneration from cultured tissues or protoplasts was conducted with the perennial, allogamous and autotetraploid Medicago sativa L., which proved amenable to regeneration via somatic embryogenesis from tissue explants (Saunders and Bingham 1972) and protoplasts (Johnson et al 1981;Rose et al 1986). Regeneration was restricted to special lines, notably Regen S, which was bred for regenerability (Bingham et al 1975). Annual Medicago species were difficult to regenerate, but work by Bingham and co-workers indicated that the Medicago genus included species with 'regenerability' genes.…”
Section: Medicago Truncatula CV Jemalong Agriculture and Biotechnologymentioning
confidence: 99%
“…Regeneration from cultured tissues or protoplasts was conducted with the perennial, allogamous and autotetraploid Medicago sativa L., which proved amenable to regeneration via somatic embryogenesis from tissue explants (Saunders and Bingham 1972) and protoplasts (Johnson et al 1981;Rose et al 1986). Regeneration was restricted to special lines, notably Regen S, which was bred for regenerability (Bingham et al 1975). Annual Medicago species were difficult to regenerate, but work by Bingham and co-workers indicated that the Medicago genus included species with 'regenerability' genes.…”
Section: Medicago Truncatula CV Jemalong Agriculture and Biotechnologymentioning
confidence: 99%
“…The explants were plated on SH induction medium lacking acetosyringinone but with 500 mg L Ϫ1 claforan and 50 mg L Ϫ1 kanamycin. Somatic embryos were matured on BOi2Y development medium (Bingham et al, 1975) containing 50 g L Ϫ1 Suc but no growth regulators or antibiotics.…”
Section: Plant Transformationmentioning
confidence: 99%
“…The paired somatic. heart somatic *cot (b) monosomes and small polysomes (fractions [5][6][7][8][9], and (c) large polysomes (fractions [10][11][12][13][14][15][16][17][18][19][20][21][22] were used for northern blot analysis against probes for the major 1 Figure 5 show the synthesis of proteins from polysomal mRNAs and those in the mRNP fraction extracted from the transition stages of developing somatic and zygotic embryos, i.e. when the patterns of storage protein synthesis change (Fig.…”
Section: Analysis Of Cell-free Translational Products Of Polysomal Anmentioning
confidence: 99%